PERAN ASPEK PERSONIL TENAGA KERJA TERHADAP PRODUKTIVITAS UKM GENTENG DI DESA PEJATEN - Ningsih, Ni Luh Anik Puspa; Darma, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2019)
The purpose of this study is to examine the influence of personnel (labor) factors specifically job stress and job exchausion experienced by employees on business productivity. Business productivity is explained by employee productivity (employee performance). This research was conducted in Small and Medium Enterprises (UKM) Pejaten tile craftsmen in Tabanan, Bali. The respondents in this study were 42 workers at Asih UKM. With the census sampling technique the entire population is sampled in this study. The analysis technique used in this study is multiple linear regression analysis. Based on the data processing carried out the results of work stress have a negative and significant effect on business productivity which is explained by the performance of employees at SME Asih tile craftsmen in Pejaten. Work Fatigue has a negative and significant effect on business productivity which is explained by the performance of employees at UKM Asih tile craftsmen in Pejaten.